Stressful Life Events in Different Social Contexts Are Associated With Self-Injury From Early Adolescence to Early Adulthood - Steinhoff, Annekatrin; Bechtiger, Laura; Ribeaud, Denis; Eisner, Manuel; Shanahan, Lilly (Frontiers in Psychiatry, 2020)
Self-injury often arises as a maladaptive coping strategy used to alleviate distress. Past research has typically examined how chronic stressors in a specific context are associated with self-injury. Little is known about the unique and cumulative associations between acute stressful life events that occur in different social contexts and self-injury among adolescents. This is especially the case for males, for whom the etiology of self-injury is understudied. We examine the unique and cumulative contributions of stressful life events in the contexts of adolescents’ school life, peer networks, intimate relationships, and family life to self-injurious behavior in males and females from the community. Our data comes from a prospective-longitudinal community-representative study, the Zurich Project on the Social Development from Childhood to Adulthood (z-proso). Our sample consists of 1,482 adolescents (52% male) assessed at ages 13, 15, 17, and 20. At each age, adolescents reported whether they had engaged in self-injury during the previous month. They also reported stressful life events in the school, peer, intimate relationships, and family contexts, typically since the last assessment. Stressful life events in the peer context were consistently associated with self-injury. In the contexts of school, intimate relationships, and family, some associations were age- or sex-specific. For example, mid-adolescent females were more likely than mid-adolescent males to use self-injury when faced with stressful events in school and intimate relationships. With respect to risk accumulation, females’ risk of self-injury increased with each additional life event between the ages of 13 and 17, beginning at 2+ events. This pattern did not hold for males. In early adulthood, 4+ life events were associated with an increased risk of self-injury, which suggests that the thresholds for the number of life events needed to trigger self-injury increased from adolescence to young adulthood. Our findings suggest that reducing risk of stressful events in different social contexts, and improving young people’s coping skills could help reduce their risk of self-injury. New or revised theoretical models may be needed to better understand the emergence of self-injury in males.